Ph value of infant's skin is higher on diaper area compared to nondiaper area - Nadia Wirantari; Linda Astari; Iskandar Zulkarnain (PAGEPress Publications, 2019)
Prolonged use of diaper may alter skin barrier function due to exposure to irritants from feces and urine, concurrent mechanical friction and occlusion, thus render the skin prone to inflammation and infection. Measurement of skin pH value may be used to document skin barrier function, especially in tropical countries such as Indonesia, and to expose the difference between diapered and non-diapered skin. The purpose of this study is to compare the pH value between baby's diapered and non-diapered skin. In this cross-sectional study, the skin pH of 43 healthy babies aged 6 to 12 months were measured using pH-meter on diaper and non-diaper area of the skin. pH values were documented and compared. The mean pH value of diaper area was 6,11 ± 0,72 g/m2/h (95% CI, 4,88 - 8,02) and non-diaper area was 5,91 ± 0,69 g/m2/h (95% CI, 4,53 - 7,69), with significant difference (p=0,005). pH values increased significantly on diaper area compared to nondiaper area, revealing impaired barrier function on diapered skin, despite no pathological skin changes.